Mechanism of Gegen Qinlian Decoction in the treatment of diabetic cataract based on network pharmacology and experimental validation - Juanjuan Xia; Xin Wang; Xiaomei Fu; Weihong Zhong; Wenting Wu; Liping Yu; Ruixiang Xu; Jing Tang; Ting Gui; Jing Liu; Shuhong Peng; Weifeng Zhu (Tissue and Cell, 2027)

Integrated widely targeted metabolomics and GC-IMS reveal dynamic flavor, nutritional, functional, and metabolic profiles in macadamia kernels during processing - Gangjun Guo; Xiuhua Lan; Wenting Xu; Fujun Miao; Jiarong Fu; Shangxuan Ma; Yuanmiao Wei; Xinghao Tu; Xiyong He (Food Chemistry, 2026)

Comparative effects of sodium butyrate and Artemisia seed polysaccharide on performance, and glucagon-like peptide-2 in post-weaning Ordos fine wool sheep lambs - Ding Yang; Xinshuai Bing; Lu Jin; Chunhua Zhang; Xiangxiong Zhang; Shengli Li; Chula Sa; Le Fu; Wenting Li; Haizhou Sun (Small Ruminant Research, 2026)

Multi-omics Analysis Reveals the Prognostic and Therapeutic Value of TGF-β Signaling-related Genes in Idiopathic Pulmonary Fibrosis - Chenkun Fu; Xiaoting Jing; Menglin Zhang; Yiju Cheng; Wenting Yang; Xiao Wu; Xiaojuan Chu; Xiaofeng Lu (Biochemical Genetics, 2026)

Upregulation of m6A writer WTAP by histone lactylation promotes inflammatory response via TLR2 in neutrophils - Bailu Du; Wenting Song; Yiming Zhang; Yan Yin; Yuanjie Zhou; Yi Pan; Ruwen Yang; Muxiu Jiang; Nan Shen; Qihua Fu; Jianye Zang; Yue Tao; et al. (Science China Life Sciences, 2026)

Unraveling the mechanism by which Lactiplantibacillus plantarum modulates alfalfa silage quality and antioxidant phytochemical accumulation through integrated microbiome–metabolomics analysis - Yuqian Liu; Ze Wang; Wenting Gou; Jia Fu; Mengxue Liu; Nanyi Zhang; Qiang Si; Hongmei Shang (Animal Feed Science and Technology, 2026)

Targeted screening of pancreatic lipase inhibitory peptides from quinoa protein hydrolysates by ligand fishing - Zeyue Fu; Junhao Wang; Chunxiao Wu; Jinfan Qin; Byung-Hoo Lee; Man Li; Qingjie Sun; Wenting Tang (Food Chemistry, 2025)

Microbial nitrogen removal processes under PFAS stress: mechanisms, functional evolution, and research outlook - Wenting Fu; Xianglan Ao; Yuan Zhou; Mengxue Xing; Zhilin Xing (Biodegradation, 2025)

Ginseng stem and leaf extract residue improves antioxidant and immune functions and intestinal microflora in broilers - Wenting Gou; Shaonan Liu; Yuqian Liu; Jia Fu; Wei Yuan; Mengxue Liu; Qiang Si; Nanyi Zhang; Hongmei Shang (Research in Veterinary Science, 2025)

Development and characterization of Agriophyllum squarrosum starch nanoparticles for enhanced pickering emulsification stability - Lihong Han; Xiaofan Yang; Wenting Fu; Yuanyuan Li; Zhaojun Wei; Donghong Liu; Shuang Qiu (Food Chemistry, 2025)

Synergistic bactericidal and antibiofilm effects of curcumin and nisin dual-loaded liposomes combined with photodynamic treatment on Listeria monocytogenes - Jie Zhang; Jinfan Qin; Zeyue Fu; Wenting Tang; Chuanfen Pu; Qingjie Sun (Food Chemistry, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Selectively extracting lithium from single and mixed cathode materials - Zifei Meng; Jiahui Hou; Zexin Wang; Xiaotu Ma; Panya Thanwisai; Jinzhao Fu; Zeyi Yao; Wenting Jin; Hao Zhou; Zhenzhen Yang; Yan Wang (Chemical Engineering Journal, 2025)

High co-infection burden and ICU-specific pathogen profiles in pediatric Candida albicans respiratory infections: a large-scale tNGS analysis - Ya Huang; Huideng Zhou; Jiangyang Zhao; Lishai Mo; Junming Lu; Guangbing Liu; Shuo Zhang; Yanhua Feng; Wenting Tang; Qiang Huang; Yan Chen; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

Design of protein-based carriers for curcumin with tailored particle properties: Stability and mechanistic insights - Wenting Huang; Zhiping Hong; Zhijie Fu; Chun Meng; Yuhong Mao (Food Chemistry, 2025)

PED-TRFIA: PEDV early on-site detection based on the time-resolved fluorescence ImmunoAssay - Bin Wang; Hongli Li; Rui Liang; Tingting Fu; Shusen Ji; Boya Li; Peichen Zhang; Haiyang Wu; Wenting Wang; Lianmei Bai; Xiuju Yu; Wei Hou; et al. (Analytica Chimica Acta, 2025)

Construction and Bioinformatics Analysis of ceRNA Regulatory Networks in Idiopathic Pulmonary Fibrosis - Menglin Zhang; Xiao Wu; Honglan Zhu; Chenkun Fu; Wenting Yang; Xiaoting Jing; Wenqu Liu; Yiju Cheng (Biochemical Genetics, 2025)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive form of pulmonary fibrosis of unknown etiology. Despite ongoing research, there is currently no cure for this disease. Recent studies have highlighted the significance of competitive endogenous RNA (ceRNA) regulatory networks in IPF development. Therefore, this study investigated the ceRNA network associated with IPF pathogenesis. We obtained gene expression datasets (GSE32538, GSE32537, GSE47460, and GSE24206) from the Gene Expression Omnibus (GEO) database and analyzed them using bioinformatics tools to identify differentially expressed messenger RNAs (DEmRNAs), microRNAs (DEmiRNAs), and long non-coding RNAs (DElncRNA). For DEmRNAs, we conducted an enrichment analysis, constructed protein–protein interaction networks, and identified hub genes. Additionally, we predicted the target genes of differentially expressed mRNAs and their interacting long non-coding RNAs using various databases. Subsequently, we screened RNA molecules with ceRNA regulatory relations in the lncACTdb database based on the screening results. Furthermore, we performed disease and functional enrichment analyses and pathway prediction for miRNAs in the ceRNA network. We also validated the expression levels of candidate DEmRNAs through quantitative real-time reverse transcriptase polymerase chain reaction and analyzed the correlation between the expression of these candidate DEmRNAs and the percent predicted pre-bronchodilator forced vital capacity [%predicted FVC (pre-bd)]. We found that three ceRNA regulatory axes, specifically KCNQ1OT1/XIST/NEAT1-miR-20a-5p-ITGB8, XIST-miR-146b-5p/miR-31-5p- MMP16, and NEAT1-miR-31-5p-MMP16, have the potential to significantly affect IPF progression. Further examination of the underlying regulatory mechanisms within this network enhances our understanding of IPF pathogenesis and may aid in the identification of diagnostic biomarkers and therapeutic targets.

Micro- and nanoplastics differ in particle-mucus interactions: The sight on rheological properties, barrier dysfunction and microbiota dysbiosis - Xuemei Meng; Xue Zheng; Wenting Mai; Jianying Gao; Yanli Fan; Jing Fu; Junnan Xu (Journal of Hazardous Materials, 2025)

Clinical characteristics and co-infection analysis of influenza a virus in pediatric respiratory infections: a study based on tNGS technology - Chunyun Fu; Qiang Huang; Jiangyang Zhao; Lishai Mo; Wenting Tang; Junming Lu; Yili Zhang; Xiangjun Lu; Ya Huang; Yanhua Feng; Xuehua Hu; Yanqing Tang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Orthosilicic Acid Promotes Diabetic Wound Healing Through the PI3 K/AKT/mTOR Signaling Pathway - Xinhui Wu; Jincheng Liu; Wenting Song; Lanxia Wu; Qingyang Fu; Junfei Chen; Qiu Li (Biological Trace Element Research, 2025)

Epidemiological and clinical profiles of respiratory syncytial virus infections in hospitalized children: a retrospective cohort study utilizing targeted next-generation sequencing - Chunyun Fu; Jialing Ruan; Lishai Mo; Jiangyang Zhao; Junming Lu; Ya Huang; Xuehua Hu; Qiang Huang; Yanhua Feng; Wenting Tang; Ning Zhu; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Clinical and prognostic insights into Chlamydia trachomatis in pediatric acute respiratory infections: evidence from targeted next-generation sequencing of 5,021 cases - Chunyun Fu; Huan Zhang; Xiangjun Lu; Yanhua Feng; Lishai Mo; Junming Lu; Huiping Huang; Qiang Huang; Cuihong Lu; Wenting Tang; Ruting Chen; Silin Jiang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Regulating effect of glycated rice bran protein aggregates and resultant emulsions on the gelatinization and retrogradation properties of rice starch - Yongxue Luo; Hanwen Cui; Wenting Tang; Zeyue Fu; Chuanfen Pu; Qingjie Sun (Food Hydrocolloids, 2025)

Bibliometric analysis of microplastics research: Advances and future directions (2020–2024) - Zhilin Xing; Wenting Fu; Liangjie Li; Shan Wu (Continental Shelf Research, 2025)

Oil in water emulsion stabilized by glycated rice bran protein aggregates: Effect on interfacial behavior and in vitro digestion of emulsion - Yongxue Luo; Chuanfen Pu; Jie Zhang; Zeyue Fu; Wenting Tang; Qingjie Sun (Food Hydrocolloids, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

A low-temperature co-treatment of diethylhexyl phthalate-rich polyvinyl chloride and waste copper catalyst by subcritical water (hydrothermal treatment): Dechlorination, recovery of diethylhexyl phthalate and copper - Yingying Qi; Wenting Shao; Fu-Rong Xiu (Waste Management, 2024)

Metabolic profile and antioxidant properties of grape juice subjected to long-fermentation with Lactiplantibacillus plantarum strain isolated from traditional pickled vegetables - Yanlu Li; Wenting Fu; Huiru Du; Zhideng Zhao; Lei Li; Zhigang Dong; Jun Wang (Food Bioscience, 2024)

Current trends and perspectives on aquatic-derived protein: A focus on structure-technofunctional properties relationship and application for food preservation - Jingxuan Zhou; Qiaohui Feng; Huixian Fu; Kun Ren; Wenting Shang; Chuan Li; Xiaoshuan Zhang; Thi Tuyet Nga MAI; Yanfu He (Trends in Food Science & Technology, 2024)

Oleogels based on peanut protein isolate fibrils: Structural characterization dependent on induction time and suitability in marguerite biscuits - Kexin Wang; Jie Zhang; Zeyue Fu; Yongxue Luo; Chuanfen Pu; Wenting Tang; Qingjie Sun (Food Hydrocolloids, 2024)

N-desmethyldauricine from Menispermum dauricum DC suppresses triple-negative breast cancer growth in 2D and 3D models by downregulating the NF-κB signaling pathway - Wenting Liu; Yan Yu; Tao Hou; Hongli Wei; Fangbin Lv; Aijin Shen; Yanfang Liu; Jixia Wang; Dongmei Fu (Chemico-Biological Interactions, 2024)

Study on multiscale structures and digestibility of cassava starch and medium-chain fatty acids complexes using molecular simulation techniques - Wenting Shang; Xin Li; Jinyu Du; Yuxin Guo; Dekun Fu; Yanfu He; Fei Pan; Weimin Zhang; Zhongkai Zhou (Food Research International, 2024)

Impact of ocean acidification on microzooplankton grazing dynamics - Wenting Shi; Xiaoting Fu; Yabo Han; Jiahui Qin; Jun Sun (Frontiers in Marine Science, 2024)
This study examines the potential impacts of projected atmospheric carbon dioxide ( p CO 2 ) levels reaching 800 ppm by the end of the century, focusing on ocean acidification effects on marine ecosystems in the coastal areas of Bohai. We investigated how acidification affects the grazing patterns of microzooplankton using dilution techniques and ecophysiological methods. Our findings indicate that acidic conditions shift the phytoplankton community structure, changing dominant species. Elevated CO 2 concentrations reduced grazing pressure on phytoplankton, with less steep declines in growth rates at 800 ppm CO 2 (spring: 2.43 d −1 vs. 2.16 d −1 , summer: −0.46 d −1 vs. −0.73 d −1 , autumn: −0.45 d −1 vs. −0.90 d −1 ) and significant decreases in grazing pressure percentages (%Pp from 0.84 to 0.58 and %Pi from 0.64 to 0.46). Short-term acid exposure significantly increased superoxide dismutase activity in both microplankton (from 0.03 to 0.08 U mg −1 , p<0.01) and nanoplankton (from 0.05 to 0.09 U mg −1 , p<0.001), indicating an adaptive response to oxidative stress. These results highlight that elevated CO 2 levels primarily boost phytoplankton growth by reducing microzooplankton grazing pressure, resulting in higher growth rates and a shift towards smaller-sized phytoplankton, reflecting complex short-term ecological responses to acidification. Further research is needed to understand the long-term effects of ocean acidification on microzooplankton and their role in marine secondary productivity.

A novel subcritical water synergistic co-treatment of brominated epoxy resin and copper-based spent catalysts: debromination, phenol production, and copper recovery - Fu-Rong Xiu; Haipeng Zhou; Yingying Qi; Wenting Shao (Waste Management, 2024)

Impact of environmental variables on the distribution of phytoplankton communities in the Southern Yellow Sea - Xiaoting Fu; Wenting Shi; Zishi Liu; Xingzhou Wang; Guicheng Zhang; Jun Sun (Environmental Research, 2024)

Urbanization effects on the spatial patterns of spring vegetation phenology depend on the climatic background - Peiyi Yin; Xuecao Li; Yuyu Zhou; Jiafu Mao; Yongshuo H. Fu; Wenting Cao; Peng Gong; Wanru He; Baoguo Li; Jianxi Huang; Xiaoping Liu; Zitong Shi; et al. (Agricultural and Forest Meteorology, 2024)

Synergetic treatment of waste tantalum capacitors and polyvinyl chloride by subcritical water: Tantalum recovery, benzoic acid production and dechlorination - Fu-Rong Xiu; Longsheng Zhan; Yingying Qi; Xinyue Lei; Jiali Wang; Haipeng Zhou; Wenting Shao (Process Safety and Environmental Protection, 2024)

Influence of covalent conjugates of zein peptide-phenolic acids with different hydrophobicity on performance of resultant lutein-loaded emulsion gels - Wenting Tang; Mengyao Liu; Yongxue Luo; Hanwen Cui; Zeyue Fu; Jie Zhang; Qingjie Sun; Chuanfen Pu (Journal of Food Engineering, 2024)

Highly-efficient lipid production from hydrolysate of Radix paeoniae alba residue by oleaginous yeast Cutaneotrichosporon oleaginosum - Chen Xu; Yanan Wang; Chuying Zhang; Junheng Liu; Hanqi Fu; Wenting Zhou; Zhiwei Gong (Bioresource Technology, 2024)

Microplastics reduced bioavailability and altered toxicity of phenanthrene to maize (Zea mays L.) through modulating rhizosphere microbial community and maize growth - Xiancao Chen; Xiaoyan Zheng; Wenting Fu; Anran Liu; Wenjing Wang; Gang Wang; Jing Ji; Chunfeng Guan (Chemosphere, 2023)

Metabolic diversity shapes vegetation-enhanced methane oxidation in landfill covers: Multi-omics study of rhizosphere microorganisms - Shangjie Chen; Wenting Fu; Limin Cai; Zhilin Xing; Baozhong Mou; Yongqiong Wang; Shan Wu; Tiantao Zhao (Waste Management, 2023)

An alkali-enhanced subcritical water treatment strategy of short-chain chlorinated paraffins: Dechlorination and hydrocarbons recovery - Fu-Rong Xiu; Qingyun Bai; Yingying Qi; Xinyue Lei; Ruiqi Yang; Siyi Wang; Yixiao Wang; Jiali Wang; Longsheng Zhan; Haipeng Zhou; Wenting Shao (Science of The Total Environment, 2023)

Improving the flavor of tilapia fish head soup by adding lipid oxidation products and cysteine - Huixian Fu; Qiaohui Feng; Dan Qiu; Xuanri Shen; Chuan Li; Yanfu He; Wenting Shang (Food Chemistry, 2023)

Microalgae-assisted heterotrophic nitrification-aerobic denitrification process for cost-effective nitrogen and phosphorus removal from high-salinity wastewater: Performance, mechanism, and bacterial community - Linfang Zhang; Xiaodan Huang; Wenting Chen; Guokai Fu; Zhi Zhang (Bioresource Technology, 2023)

Starch and Sugar Metabolism Response to Post-Anthesis Drought Stress During Critical Periods of Elite Wheat (Triticum aestivum L.) Endosperm Development - Chao Li; Kaiyong Fu; Wenting Guo; Xiangchi Zhang; Chunyan Li; Cheng Li (Journal of Plant Growth Regulation, 2023)

Impact of Ethylene and Abscisic Acid on Programmed Cell Death in Endosperm and Grain Filling of Wheat (Triticum aestivum L.) - Chao Li; Xiangchi Zhang; Wenting Guo; Kaiyong Fu; Chunyan Li; Cheng Li (Journal of Plant Growth Regulation, 2023)

High-efficiency promotion on dechlorination of polyvinyl chloride in subcritical water treatment by introducing waste concrete - Fu-Rong Xiu; Ruiqi Yang; Yingying Qi; Ke Zhou; Jiali Wang; Wenting Shao; Haipeng Zhou; Longsheng Zhan (Process Safety and Environmental Protection, 2023)

Sulfur dioxide may predominate in the adverse effects of ambient air pollutants on semen quality among the general population in Hefei, China - Feng Zhang; Hang Li; Wenting Xu; Ge Song; Zhanpeng Wang; Xiaohong Mao; Yiqiu Wei; Mengyang Dai; Yuying Zhang; Qunshan Shen; Feifei Fu; Jing Tan; et al. (Science of The Total Environment, 2023)

The potential roles of carotenoids in enhancing phytoremediation of bisphenol A contaminated soil by promoting plant physiology and modulating rhizobacterial community of tobacco - Wenting Fu; Xiaoyan Zheng; Xiancao Chen; Wenjing Wang; Anran Liu; Jing Ji; Gang Wang; Chunfeng Guan (Chemosphere, 2023)

Combined application of a PGPR strain Methylophilus sp. FP-6 and adenine to enhance the phytoremediation potential of tobacco: oxybenzone remediation, plant response and rhizosphere bacterial community adaptation - Wenjing Wang; Anran Liu; Xiaoyan Zheng; Xiancao Chen; Wenting Fu; Gang Wang; Jing Ji; Sheyan Pei; Chunfeng Guan (Plant and Soil, 2023)

Phytoremediation potential, antioxidant response, photosynthetic behavior and rhizosphere bacterial community adaptation of tobacco (Nicotiana tabacum L.) in a bisphenol A-contaminated soil - Wenting Fu; Xiancao Chen; Xiaoyan Zheng; Anran Liu; Wenjing Wang; Jing Ji; Gang Wang; Chunfeng Guan (Environmental Science and Pollution Research, 2022)

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

The construction of high precision geostrophic currents based on new gravity models of GOCE and satellite altimetry data - Wenyan Sui; Junru Guo; Jun Song; Zhiliang Liu; Meng Wang; Xibin Li; Yanzhao Fu; Yongquan Li; Yu Cai; Linhui Wang; Lingli Li; Xiaofang Guo; et al. (Acta Oceanologica Sinica, 2021)

Two-Stage Multi-Water Sources Allocation Model in Regional Water Resources Management under Uncertainty - Dong Liu; Wenting Liu; Qiang Fu; Yongjia Zhang; Tianxiao Li; Khan M. Imran; Faiz M. Abrar (Water Resources Management, 2017)

Evaluating common land model energy fluxes using FLUXNET data - Xiangxiang Zhang; Yongjiu Dai; Hongzhi Cui; Robert E. Dickinson; Siguang Zhu; Nan Wei; Binyan Yan; Hua Yuan; Wei Shangguan; Lili Wang; Wenting Fu (Advances in Atmospheric Sciences, 2017)

Analysis of the Appropriate Development Scale of Regional Paddy Field Under the Restriction of Water Resources - Dong Liu; Dan Zhao; Qiang Fu; Tianxiao Li; Muhammad Imran Khan; Wenting Liu; Faiz M. Abrar (Agricultural Research, 2016)

Characterization, expression and silencing by RNAi of p53 from Penaeus monodon - Wenting Dai; Lihua Qiu; Chao Zhao; Mingjun Fu; Zhenhua Ma; Falin Zhou; Qibin Yang (Molecular Biology Reports, 2016)

Polymorphism of DEFA in Chinese Han population with IgA nephropathy - Ricong Xu; Shaozhen Feng; Zhijian Li; Yonggui Fu; Peiran Yin; Zhen Ai; Wenting Liu; Xueqing Yu; Ming Li (Human Genetics, 2014)